PROBLEMS ENCOUNTERED WITH ORTHODONTIC MOVEMENT OF IMPACTED MAXILLARY CANINES (Laporan Kasus) - Chandra Wigati (Faculty of Dentistry, Universitas Indonesia, 2015)
Maxillary permanent canines are impacted in about 2% of orthodontic patients, second only in frequency of impaction to third molars. Bringing an impacted canine into the arch creates a set of problems, primarily because it usually a long way from the line of occlusion. Four cases of impacted maxillary canines are presented to show some of the problems encountered during orthodontic traction of these teeth. The cases were treated using a preadjusted edgewise appliances. Careful judgement are needed to treat impacted maxillary canines successfully and to minimize discouraging side effects that often occurs during the procedure.